KESEJAHTERAAN PETANI PADI SAWAH DI KAWASAN AMOHALO KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Faradillah, Vera; Mappasomba, Musadar; Salahuddin, Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The purpose of this study is to evaluate the condition of rice farmers living in Baruga Village, Baruga District, Kendari City. The problem observed is the imbalance between the region's status as a rice production center and the inconsistent and fluctuating level of farmer welfare. Although Baruga Village has approximately 450 hectares of agricultural land and makes a significant contribution to rice cultivation in Kendari City, farmers' income remains uncertain each harvest season. This uncertainty negatively impacts their overall welfare. The welfare of these farmers is also measured by the Farmer Exchange Rate (NTP), which evaluates the gap between the income earned by farmers from their harvest and the costs incurred for production. An NTP value below 100 indicates that farmers are experiencing losses or decreased purchasing power, thus causing a decline in their welfare. The research findings show that most farmers in Baruga Village are included in the prosperous category. Farmers of productive age, with extensive farming experience, and supporting larger families often exhibit increased motivation and a sense of responsibility, which positively impacts their income and overall well-being. This study emphasizes the need for governments and policymakers to focus more on farmer characteristics when developing empowerment initiatives aimed at improving farmer welfare in rice-producing regions.